Sub-National Location Determinants of Inward Foreign Direct Investment: A Statistical Appraisal Across Regions in India - Chakraborty, Gourab (Asian Economic and Financial Review, 2018)
There is a general proposition that availability of infrastructure facilities largely determines the locations of investment projects and also that Foreign Direct Investment (FDI) can be Resource seeking, Efficiency seeking and clusters in a region where there is already existing FDI. I employed a panel dataset consisting of 16 groups of Indian states over the period from 2001-02 to 2016-17, with the aim to identify the infrastructure, resource, market, and agglomeration specific factors that contribute to the wide-scale heterogeneity in the per capita FDI inflows across the Indian States. My results suggest that the availability of roads, ports and telecommunication infrastructure predominantly influenced the variations in the FDI inflows across states than any other infrastructure specific determinant. The findings indicate that the efficiency of labor was the highest motivation among resource specific factors for investors. Moreover, higher tax disincentive, the presence of the SEZs, and agglomeration economies are found to be statistically significant. Lastly, the per capita FDI is not found to be market seeking in nature.